1992
DOI: 10.1073/pnas.89.5.1621
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cl- channels in normal and cystic fibrosis airway epithelial cells by extracellular ATP.

Abstract: The rate of Cl- secretion by human airway epithelium is determined, in part, by apical cell membrane Cl- conductance. In cystic fibrosis airway epithelia, defective regulation of Cl- conductance decreases the capability to secrete Cl-. Here we report that extracytosolic ATP in the luminal bath of cultured human airway epithelia increased transepithelial Cl- secretion and apical membrane Cl- permeability. Single-channel studies in excised membrane patches revealed that ATP increased the open probability of outw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(66 citation statements)
references
References 43 publications
5
60
1
Order By: Relevance
“…Data presented in this study showed that ATP (adenine nucleotide) and UTP (uridine nucleotide) produced approximately equal membrane depolarization upon their exogenous application, indicating the expression of P2Y 2 receptors on the longitudinal smooth muscle of chicken anterior mesenteric artery. Secondary to activation of PLC and mobilization of Ca 2 þ , the P2Y 2 -like receptor mediates the opening of Ca 2 þ -sensitive Cl À channels in airway epithelia Stutts et al, 1992) and avian exocrine salt gland cells (Martin & Shuttleworth, 1995). Similarly, our data showed that the Cl À channel blocker NPPB significantly inhibited the EFS-evoked depolarization as well as the exogenous application of ATP and 2-MeSATP.…”
Section: Khalifa Et Alsupporting
confidence: 61%
“…Data presented in this study showed that ATP (adenine nucleotide) and UTP (uridine nucleotide) produced approximately equal membrane depolarization upon their exogenous application, indicating the expression of P2Y 2 receptors on the longitudinal smooth muscle of chicken anterior mesenteric artery. Secondary to activation of PLC and mobilization of Ca 2 þ , the P2Y 2 -like receptor mediates the opening of Ca 2 þ -sensitive Cl À channels in airway epithelia Stutts et al, 1992) and avian exocrine salt gland cells (Martin & Shuttleworth, 1995). Similarly, our data showed that the Cl À channel blocker NPPB significantly inhibited the EFS-evoked depolarization as well as the exogenous application of ATP and 2-MeSATP.…”
Section: Khalifa Et Alsupporting
confidence: 61%
“…Nucleotides acting through the P2Y 2 receptor have been shown to induce Cl − secretion in airway epithelial cells that is not dependent on the cystic fibrosis transmembrane-conductance regulator (5), and P2Y 2 receptor ligands have been proposed as novel class of medication for treatment of retinal detachment (6) and improved mucociliary clearance in clinical conditions such as cystic fibrosis (7).…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological strategies aimed at conquering the CF defect in Cl-secretion have in recent years focused on discovering new agents that would stimulate epithelial Cl -secretion through an alternate cAMP-independent mechanism (for review see reference 4). A number of purinoceptor agonists have recently been shown to enhance Cl-secretion in CF epithelial cells (5)(6)(7)(8). P2 purinoceptor agonists ATP and UTP, in particular, have been tested in clinical trails (9).…”
Section: Introductionmentioning
confidence: 99%